Changes in drinking days among United States adults during the COVID‐19 pandemic. (12th July 2021) - Nordeck, Courtney D.; Riehm, Kira E.; Smail, Emily J.; Holingue, Calliope; Kane, Jeremy C.; Johnson, Renee M.; Veldhuis, Cindy B.; Kalb, Luther G.; Stuart, Elizabeth A.; Kreuter, Frauke; Thrul, Johannes
Abstract: Aims: To examine changes in drinking behavior among United States (US) adults between March 10 and July 21, 2020, a critical period during the COVID‐19 pandemic. Design: Longitudinal, internet‐based panel survey. Setting: The Understanding America Study (UAS), a nationally representative panel of US adults age 18 or older. Participants: A total of 4298 US adults who reported alcohol use. Measurements: Changes in number of reported drinking days from March 11, 2020 through July 21, 2020 in the overall sample and stratified by sex, age, race/ethnicity, household structure, poverty status, and census region. Findings: Compared with March 11, the number of drinking days per week was significantly higher on April 1 by an average of 0.36 days (95% CI = 0.30, 0.43), on May 1 by an average of 0.55 days (95% CI = 0.47, 0.63), on June 1 by an average of 0.41 days (95% CI = 0.33, 0.49), and on July 1 by an average of 0.39 days (95% CI = 0.31, 0.48). Males, White participants, and older adults reported sustained increases in drinking days, whereas female participants and individuals living under the federal poverty line had attenuated drinking days in the latter part of the study period. Conclusions: Between March and mid‐July 2020, adults in the United States reported increases in the number of drinking days, with sustained increases observed among males, White participants, and older adults.